New Insights on the Raman and SERS Spectra of Luteolin under Different Excitation Conditions: Experiments and DFT Calculations - Marilena Ricci; Emilio Mario Castellucci; Silvia Innocenti; Maurizio Becucci (Chemosensors, 2023)
We have studied, by density functional theory, the interaction between luteolin and Ag, devising two complexes where an Ag14 cluster faces two different sites of the molecule. The two sites are identified as quinoid-like and cathecol-like, and the complexes are CPLX1 and CPLX2, respectively. Raman and SERS spectra of luteolin were measured at different excitation wavelengths. Luteolin solid samples from different suppliers have different Raman spectra, possibly associated with different arrangements in the solids. These spectra are well reproduced by our DFT calculations. Assignment of the vibrational modes of luteolin and of the two luteolin–Ag14 complexes is obtained thanks to decomposition of the normal coordinates in terms of internal coordinates. The calculated Raman spectrum for CPLX1 seems to better reproduce the experimental SERS spectra. CPLX2 furnishes a spectrum still resembling that of luteolin in the high frequency region and is possibly responsible for some weak bands in the 1400–1700 cm−1 range that cannot be accounted by the CPLX1 system. SERS spectra are dependent on the Raman excitation wavelength. The calculation of the electronic spectrum suggests the presence of charge-transfer states, which might be responsible for the changes in the SERS spectra.